Reconceptualizing the Concept of Hegemony in Malay Political Culture: (Menilai Semula Konsep Hegemoni dalam Budaya Politik Melayu) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2017)
Waadat or social contract in Sejarah Melayu (The Malay Annals) is a significant element in traditional Malay political culture. This agreement has shaped the Malay political arena, before, during and post-independence. The impact of colonial construction on the Malay political culture has brought about the transformation of the political culture system from obedience towards the Malay sultans to the British colonials and later to local Malay leaders. The study found that the nature of Malay obedience can only be vaguely described using the concept of hegemony alone. The concept of natural obedience has been applied to discuss the issue of the instinctive Malay obedience towards their rulers.Keywords: Waadat, social contract, political culture, obedience